The Implementation of "لتعارفوا" Concept in Speech Code Adaptation in Boarding Based University - Muhammad Fajar Arafat; Rila Setyaningsih (Sahafa Journal of Islamic Communication, 2018)
AbstractIn society, culture plays an important role to keep the identity of a region and particular group. Therefore, the good intercultural communication ability is needed. Basically, there is a communication within a culture and vice versa. Both of them cannot be separated. The students of University of Darussalam Gontor (UNIDA Gontor) have their own speech code. It was formed because the students used Arabic or English in their daily interaction. The language and speech code in UNIDA Gontor are not only used by PMDG’s student alumni, but also those used by the regular high school alumni which is called as Non-KMI students. These students usually do not speak Arabic before. There are not many differences between Speech code of UNIDA Gontor and PMDG’s, because the majority of students is PMDG’s student alumni. Finally, the speech code can be accepted by the Non-KMI students as the subject in this research by adaptation. The adaptation is aimed to build a relation and to interact with the surroundings easily. This research used a qualitative descriptive research. The result of the research revealed that there are 4 stages of cultural adaptation; honeymoon, frustration, readjustment, and resolution. Meanwhile, the subject went through the phase of assimilation, integration, and combined relation method as their speech code adaptation to build a relation and knowing each otherلِتَعَارَفُو as Allah command to the mankind in Al Hujurat verse 13.Keyword: Adaptation, Speech Code, لِتَعَارَفُو